If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 + 50x = 0 Solving 35 + 50x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 50x = 0 + -35 Combine like terms: 35 + -35 = 0 0 + 50x = 0 + -35 50x = 0 + -35 Combine like terms: 0 + -35 = -35 50x = -35 Divide each side by '50'. x = -0.7 Simplifying x = -0.7
| (4x+13)+(8x-5)= | | 7(8x+5)= | | 3x-5x=-9+x | | 2x^4+7=47 | | 2a+7b-3b+a= | | m+50x=35 | | f(x)=-16x+160x | | 6x+x-8=6x+5 | | 3.2=125x | | 8m-2m=72 | | 5g-5=7 | | -5=-19-n/7 | | 13x-60=83 | | x^6+7x^5+2x^4+9x^3+10x^2-12x-15=0 | | 2/5(x-15)=500 | | c/7+5=-6 | | 24k^2=-24k | | 3x-4x+x-6+2x= | | 8x^2+72a-81=0 | | v/4-9=-3 | | 44-17x=15.60 | | (x+21)+2x=136 | | 2x^2-2x=3x^2-9x | | 180=a+2a+15+a-35 | | (x+21)-2x=136 | | -2=(-2x-8) | | 3/4(8b-4)=-2 | | 2y^2-8y+9-12y^2-8y+3= | | 4(-a+4)=12 | | 3x+12=12x-13 | | x^2+4=2x+7 | | -(5-3x)-(5-3x)= |